2022
DOI: 10.3171/2022.1.jns212449
|View full text |Cite
|
Sign up to set email alerts
|

Pretherapeutic functional connectivity of tractography-based targeting of the ventral intermediate nucleus for predicting tremor response in patients with Parkinson’s disease after thalamotomy with MRI-guided focused ultrasound

Abstract: OBJECTIVE Tractography-based direct targeting of the ventral intermediate nucleus (T-VIM) is a novel method that provides patient-specific VIM coordinates. This study aimed to explore the accuracy and predictive value of using T-VIM in combination with tractography and resting-state functional connectivity techniques to perform magnetic resonance imaging–guided focused ultrasound (MRgFUS) thalamotomy as a treatment of Parkinson’s disease (PD). METHODS PD patients underwent MRgFUS thalamotomy and were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Furthermore, previous studies have shown that pre-therapeutic FC was a powerful fMRI predictor of tremor relief after thalamotomy. 12,33 In our study, preoperative FCs of left PoCG-right SMG, left PoCG-right SPG, and right PoCG-left PreCG were also found to be negatively correlated with postoperative tremor score alteration ratios, including hand tremor score and CRST-B score. This finding suggests that preoperative FC can predict postoperative improvements in hand tremor and specific functional activities such as writing, pouring, and drawing.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, previous studies have shown that pre-therapeutic FC was a powerful fMRI predictor of tremor relief after thalamotomy. 12,33 In our study, preoperative FCs of left PoCG-right SMG, left PoCG-right SPG, and right PoCG-left PreCG were also found to be negatively correlated with postoperative tremor score alteration ratios, including hand tremor score and CRST-B score. This finding suggests that preoperative FC can predict postoperative improvements in hand tremor and specific functional activities such as writing, pouring, and drawing.…”
Section: Discussionsupporting
confidence: 58%
“…11 Pre-therapeutic FCs between tractography-based VIM and ipsilateral sensorimotor cortex, subthalamic nucleus, and the visual area were found to be positively correlated with tremor control. 12 As a result, we collected longitudinal rs-fMRI data from patients with ET to investigate the characteristics of brain functional alteration after MRgFUS. First, we measured the local brain activity metrics (fALFF and regional homogeneity) to explore significant functional changes at 6 months after MRgFUS thalamotomy.…”
mentioning
confidence: 99%
“…[8] Since the first report of MRgFUS for the treatment of PD in 2014, the field of MRgFUS has become a research hotspot. [9][10][11] Reviews have confirmed the effectiveness of MRgFUS-mediated thermal ablation. [12] Furthermore, non-thermal effects mediated by MRgFUS are gradually being implemented, such as the cavitation effect and neuromodulation.…”
Section: Magneticmentioning
confidence: 94%
“…Functional neurosurgery has developed rapidly in recent years [8] . Since the first report of MRgFUS for the treatment of PD in 2014, the field of MRgFUS has become a research hotspot [9–11] . Reviews have confirmed the effectiveness of MRgFUS-mediated thermal ablation [12] .…”
Section: Introductionmentioning
confidence: 99%
“…11,14,16 MRgFUS thalamotomy was pioneered for clinical use in ET and tremor-predominant PD in landmark clinical trials. 14,16 MR thermometry and, more recently, adjunctive MR tractography 17 can be used to focus the intracranial delivery of acoustic energy onto the stereotactic coordinates of the Vim. Tremor improvement rates are typically near 100% immediately after the procedure, 14,[18][19][20] as seen in this study, where 95% of patients experienced immediate improvement in their symptoms.…”
Section: Rationale For Vim Mrgfus In Pdmentioning
confidence: 99%